Ask the expert…. - Croser, Joe (Architects' Journal, 2004)
Answers questions from a small firm of architects in Wales on two- and three-dimensional parametric modeling in architectural design. Features of TurboCAD; Recommendation for Architectural Desktop; Computerization of processes through true data sharing; ArchiCAD features; Suggestion of asking discounts and assistance from Autodesk; Cost issues.